2020
DOI: 10.3390/info11090444
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Major Selection Motivations on Dropout, Academic Achievement and Major Satisfactions of College Students Majoring in Foodservice and Culinary Arts

Abstract: This study is aimed at figuring out the effects of major selecting motivation on dropout, academic achievement, and major satisfactions of college students majoring in foodservice and culinary arts. To accomplish this, an empirical survey was conducted through a structural equation model. These findings showed that students are likely to drop out of college due to a career change or major maladjustment if they decide their major in consideration of college reputation or department recognition rather than their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…This lack of support leads to many students facing confusion, depression, and other mental health challenges as they struggle to pave a path toward a prosperous future [42,43]. Making an ill-informed decision about one's academic or career pursuits can result in severe consequences, such as dropping out of school [5], poor job performance, decreased community involvement, and, ultimately, the hindrance of society's growth.…”
Section: The Impact Of Educational Counseling On Individuals and Societymentioning
confidence: 99%
See 1 more Smart Citation
“…This lack of support leads to many students facing confusion, depression, and other mental health challenges as they struggle to pave a path toward a prosperous future [42,43]. Making an ill-informed decision about one's academic or career pursuits can result in severe consequences, such as dropping out of school [5], poor job performance, decreased community involvement, and, ultimately, the hindrance of society's growth.…”
Section: The Impact Of Educational Counseling On Individuals and Societymentioning
confidence: 99%
“…It reinforces their decision-making skills and assists them in finding their own path rather than offering instructions or readymade solutions [2]. Educational counseling has a profound impact on student's lives and futures [3], as the choice of a specific field of study upon entering higher education holds immense weight in shaping a student's career path and can significantly impact the likelihood of securing employment in a related field, as well as the potential for long-term career growth and success [4][5][6]. This makes educational counseling a fundamental component in establishing a smooth connection between the realms of academia and the professional sphere [7].…”
Section: Introductionmentioning
confidence: 99%
“…This paper aims to identify what are factors that affect student's decision in selecting industry majors to study. Kim (2020) aimed at figuring out the effects of major selecting motivation on dropout, academic achievement, and major satisfactions of college students majoring in food service and culinary arts. To accomplish this, an empirical survey was conducted through a structural equation model.…”
Section: Introductionmentioning
confidence: 99%
“…According to Whibbs and Holmes (2019), individuals often choose to attend culinary school for intrinsic reasons (e.g., a connection to food). Soo Kim (2020) found that students who pursue college majors based on extrinsic factors such as family influence or potential earnings alone are more likely to change majors or drop out. The data also reflects that, although most participants initially chose to follow other college majors or career paths before turning to culinary, each participant cited their passion for culinary and their perception that a culinaryrelated career would increase their chances of career satisfaction as additional motivating factors.…”
Section: Decision To Enroll In Culinary Schoolmentioning
confidence: 99%